Fallen angels and forgotten heroes: A descriptive qualitative study exploring the impact of the angel and hero narrative on critical care nurses. Issue 1 (January 2023) - Stokes-Parish, Jessica; Barrett, David; Elliott, Rosalind; Massey, Deb; Rolls, Kaye; Credland, Nicki
Abstract: Background: During the COVID-19 pandemic, the use of the labels 'heroes' and 'angels' to describe nurses (and especially critical care nurses) became prevalent. While often well intentioned, the use of these labels may not be the most positive image of nurses and the nursing profession. Critical care nurses have not previously been given the opportunity to provide their perceptions of the angel/hero narrative and the impact this may have on their practice and working environments. Objectives: The objectives of this study were to explore the perspectives of critical care nurses and discover their perceptions about the angel/hero narrative and its impact on their clinical practice, safe working environments, and professional development during the COVID-19 pandemic. Methods: A semistructured qualitative virtual interview study was conducted with critical care nurses from the United Kingdom, Australia, and North America. Digital audio data were transcribed verbatim. Thematic analysis of the transcribed data was performed. The COREQ guidelines were used to report the study. Findings: Twenty-three critical care nurses located in the United Kingdom, Australia, and North America participated. Four themes were synthesised: history repeating, gender stereotypes, political pawns, and forgotten heroes. Conclusions: Critical care nurses did not perceive the hero and angel labels positively. Participants were concerned about unrealistic expectations, potential safety workplace risks, and poor remuneration related to these narratives. Participants perceived that context and intention were important in the interpretation of these narratives; they spoke with pride about their work and called for improved representations of their role, recognition, and work conditions.